Post-COVID-19 Asia will grow strongly in 2021 but structural problems continue to pile up - Alicia Garcia Herrero (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2021)
2020 was a terrible year for Asia but for some countries less than for others. Countries recovered divergently with some managing to grow positively notwithstanding the pandemic, namely mainland China, Taiwan, and Vietnam. The rest of Asia had a hard time, facing problems such as current-account deficit, tourism reliance, and limited fiscal and monetary space. This article discusses the unevenness of COVID-19 and the divergent recovery of Asian economies in the post-COVID-19 era.
Keywords: E52; E62; F50; 330; COVID-19; Asian economies; fiscal and monetary policy; US–China relations